Democracia autoritaria: Alberto Fujimori y la opinión pública - Pérez Crespo, Carlos Eduardo (Revista Latinoamericana de Opinión Pública, 2010)
The present research develops a study regarding authoritarian altitudes of public opinion in circumstances of political, economic and social crisis. Therefore, we analyse the Alberto Fujimori’s coup d’ état of April 1992 in Peru. Besides, we compare this juncture with other situations in which crisis has been controlled and, as a consequence, public opinion is more preoccupied about issues like corruption, political economy, etc. Our article states that the challenge in the research about Latin America should be not about wether people has or not an authoritarian political culture, but in search of an understanding of state of affairs of crisis and its outcomes in public opinion.